Функції біографічного наративу в історіографічній металітературі ("Музей покинутих секретів" О. Забужко) - Гребенюк, Тетяна Володимирівна; Grebenyuk, T. V. (My University, 2014)
Статтю присвячено аналізові специфіки функціонування біографічного наративу в структурі оповіді історіографічної металітератури. Сучасна українська проза на історичну тематику розглядається в контексті світової постмодерної історіографічної традиції. На матеріалі роману О. Забужко «Музей покинутих секретів» проводиться аналіз засобів творення біографічного наративу й особливостей його впливу на читача. The article is devoted to analysis of specific of the biographical narrative functioning in the structure of the historiographic metafiction narrative. Modern Ukrainian historical prose is considered in the context of the global postmodern historiographical tradition. Means of the biographical narrative forming and main characteristics of its impact on the reader are analyzed on the material of the O. Zabuzhko’s novel «Museum of Abandoned Secrets». Two main biohrams of the writer’s narrative are pregnancy and betrayal – they are the keys to the comprehension of the Ukrainian woman destiny. Amplification of the same events and circumstances in the three women’s narratives (Gelya’s, Vlada’s and Daryna’s) underlines significance of this biohrams.
Functions of the Biographical Narrative in the Historiographic Metafiction («The Museum of Abandoned Secrets» by O.Zabuzhko)
Keywords: історіографічна металітература; фікціональне/фактуальне; біографічний наратив; тезаурус; біограма; historiographic metafiction; fictional/factual; biographical narrative; thesaurus; biohram